2020
DOI: 10.1007/s11356-020-10192-6
|View full text |Cite|
|
Sign up to set email alerts
|

Ligninolytic enzyme involved in removal of high molecular weight polycyclic aromatic hydrocarbons by Fusarium strain ZH-H2

Abstract: The capacity of Fusarium sp. strain ZH-H2 to secret lignin peroxidase (LiP), laccase (Lac), and manganese peroxidase (MnP) and degrade high molecular weight polycyclic aromatic hydrocarbons (HMW-PAHs) was studied. When the fungus was grown in control mineral salt medium for 4 days, LiP and Lac activities were detected at 8871 U L −1 and 5123 U L −1 , respectively. In the presence of HMW-PAHs as the sole carbon source, only LiP activity was detectable, and LiP activity had significantly reduced HMW-PAHs at day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Their ndings contrasted with those of a previous study (Wu et al 2010), which used a strain of Fusarium solani capable of removing 40% anthracene (ANT) and 60% benz[a]anthracene (BAA) after 40 days. The latter study concluded that the differences between their results, despite using fungi in the same genus, were that different strains created variable effects in the levels, amounts, and types of metabolic enzymes (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Their ndings contrasted with those of a previous study (Wu et al 2010), which used a strain of Fusarium solani capable of removing 40% anthracene (ANT) and 60% benz[a]anthracene (BAA) after 40 days. The latter study concluded that the differences between their results, despite using fungi in the same genus, were that different strains created variable effects in the levels, amounts, and types of metabolic enzymes (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…This variance is the result of these isolates being of the same genus but different strains. The enzymatic capabilities of a speci c strain of Fusarium ZH-H2 vary depending on culture conditions and the presence of PAHs, according to one study (Zhang et al 2020). According to the study's ndings, the strain could produce both lignin perox-idase (LiP) and laccase in mineral salt medium, but when exposed to HMW-PAHs, only LiP was secreted and detected.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of PAHs by ligninolytic fungi have been extensively studied in the past few years [ 151 ], especially in white rot fungi. These fungi produce extracellular peroxidases which are responsible for the initial oxidation of PAHs [ 152 ]. The principal mechanism of biodegradation used by white rot fungi relies on the lignin degradation system which involves extra-cellular lignin modifying enzymes (LMEs), displaying reduced substrate-specificity.…”
Section: Fungi-mediated Degradation Of Petroleum Hydrocarbonsmentioning
confidence: 99%
“…Penicillium , Fusarium , Trichoderma , and Aspergillus genera belonging to the Ascomycota division, are well-known filamentous fungi capable of producing extracellular enzymes. Their crucial role in efficiently breaking down complex plant cell wall components has been extensively studied and optimized at different scales [ 33 - 36 ]. However, the development and widespread industrial use of lignocellulolytic enzymes face several limitations and challenges.…”
Section: Introductionmentioning
confidence: 99%